Percutaneous atrial septal defect closure in infant weighing (Medical Journal of Indonesia, 2020)
Percutaneous closure has become a preferred treatment for secundum atrial septal defect (ASD). However, this approach remains challenging in treating small infant weighing <10 kg because of procedure-related complications. The closure of ASD in other congenital anomalies, such as a bilateral superior vena cava (SVC), should be cautiously conducted. A 15-month-old boy with a body weight of 8 kg was diagnosed with secundum ASD (911 mm in diameter), residual pulmonary stenosis, and bilateral SVC. Transcatheter closure of ASD was successfully performed by using a 12 mm CeraFlex occluder device (Lifetech Scientific Corporation). Post-procedural examination showed good results without any impingement to the adjacent structure. Therefore,the transcatheter closure of ASD in infant weighing <10 kg and having bilateral SVC is technically feasible and safe.